2005
DOI: 10.1007/s10165-004-0356-8
|View full text |Cite
|
Sign up to set email alerts
|

HLA-B52-positive vasculo-Beh�et disease: usefulness of magnetic resonance angiography, ultrasound study, and computed tomographic angiography for the early evaluation of multiarterial lesions

Abstract: We report a case of HLA-B52-positive Behçet disease accompanied by multiarterial lesions. A 24-year-old woman was suffering from sporadic high fever and recurrent oral and genital ulcers, and laboratory data revealed severe inflammation. A diagnosis of Behçet disease was made. Magnetic resonance angiography, ultrasound study, and computed tomographic angiography demonstrated multiarterial lesions that had caused no symptoms. These noninvasive examinations were extremely useful in evaluating asymptomatic early … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…The etiology and pathogenicity of Behçet's disease are still unknown; the onset of the disease is suggested to be associated with HLA-B51. Some reports have shown cases of HLA-B52(+) Behçet's disease ( 3 ). Furthermore, various systemic manifestations can occur, including arthritis, gastrointestinal lesions, neurologic symptoms, and cardiovascular complications.…”
Section: Discussionmentioning
confidence: 99%
“…The etiology and pathogenicity of Behçet's disease are still unknown; the onset of the disease is suggested to be associated with HLA-B51. Some reports have shown cases of HLA-B52(+) Behçet's disease ( 3 ). Furthermore, various systemic manifestations can occur, including arthritis, gastrointestinal lesions, neurologic symptoms, and cardiovascular complications.…”
Section: Discussionmentioning
confidence: 99%
“…There is no specific diagnostic test for BD, but the onset of the disease is suggested to be associated with HLA-B51. Although our patient had HLA-B52 which is associated with TA, some reports have shown cases of HLA-B52 positive BD [7]. In this case, the pathologic findings of the aortic VA at the first AVR, and the aortic wall tissue at the valve detachment revealed chronic active inflammation with neutrophil infiltration and fibrosis material with granulomas without evidence of infection.…”
Section: Discussionmentioning
confidence: 50%
“…In this case report, it was reported that in a young patient with acute phase reactants elevation, prominent arterial lesions were detected while the patient was still asymptomatic with early vascular investigations, and a diagnosis of vasculo-BS was made. 14 In summary, it is obvious that there is no doubt in the diagnosis of BS with recurrent oral aphthous lesions, previous DVT, positive pathergy, and HLA-B51 tests in our patient. Of course, the coexistence of the diagnoses of BS and TAK may come to mind in this patient.…”
Section: Discussionmentioning
confidence: 51%